Accounting Information System for Palm Production Results at Cost of Goods Sold at Ptpn IV (Persero) Medan - Tarmika (Marqcha Institute, 2022)
PTPN IV is a State-Owned Enterprise (BUMN) engaged in the agro-industry business. PTPN IV (Persero) Medan manages plantations and manages palm oil commodities which includes managing areas and plants, gardens, seeds and maintenance of yielding plants, managing commodities into industrial raw materials. An accounting information system is a system that aims to collect and process data and report information related to financial transactions in a company. The important role of information systems in the business activities of a company is no longer in doubt. Supported by a good information system, a company will have a competitive advantage so that it can compete with other companies. The calculation of the cost of goods sold for palm oil production at PTPN IV (Persero) still uses a semi-computerized system so that errors often occur in calculating the cost of goods sold, a computerized system is needed so that transactions run well. This information system was built using the Visual Basic programming language and SQL Server as the database